2021
DOI: 10.1177/0269881120985102
|View full text |Cite
|
Sign up to set email alerts
|

Two randomized, double-blind, placebo-controlled trials and one open-label, long-term trial of brexpiprazole for the acute treatment of bipolar mania

Abstract: Background: Brexpiprazole is a dopamine/serotonin receptor partial agonist (D2, 5-HT1A) and antagonist (5-HT2A) approved for treatment of schizophrenia and major depressive disorder (adjunct to antidepressants). Aims: This study aimed to investigate brexpiprazole as monotherapy in acute mania (bipolar I disorder) in two short-term (ST) studies (study 080 and study 081) and one open-label (OL) extension (study 083). Methods: ST studies were three-week randomized, double-blind, flexible dose (2–4 mg/day), placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Contrary to monoamine transporter inhibiting antidepressants, the effects of mood-stabilizing antipsychotics on astroglial transmission associated with Cx43 have remained to be clarified [ 9 , 43 , 44 ]. To explore the novel mood-stabilizing mechanisms, the present study determined the effects of mood-stabilizing antipsychotics, CLZ, QTP and BPZ [ 54 , 55 , 56 , 57 ] on Cx43 expression and Cx43 containing hemichannel using primary cultured rat cortical astrocytes. The results in this study, are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to monoamine transporter inhibiting antidepressants, the effects of mood-stabilizing antipsychotics on astroglial transmission associated with Cx43 have remained to be clarified [ 9 , 43 , 44 ]. To explore the novel mood-stabilizing mechanisms, the present study determined the effects of mood-stabilizing antipsychotics, CLZ, QTP and BPZ [ 54 , 55 , 56 , 57 ] on Cx43 expression and Cx43 containing hemichannel using primary cultured rat cortical astrocytes. The results in this study, are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…CLZ is established the sole approval antipsychotic agent for the treatment of antipsychotics-resistant schizophrenia and one of the most effective antipsychotics [ 74 ]. Another meta-analysis study reported that CLZ, BPZ and QTP therapies for the management of acute phase of bipolar disorder and bipolar depression were efficacious [ 54 , 55 , 56 , 57 , 75 , 76 ]. Taken together with clinical findings, the present results suggest the candidate mechanisms that enhanced functional astroglial Cx43 is, at least partially, involved in the mood-stabilizing antipsychotic actions of CLZ, QTP and BPZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While cariprazine proved to be efficacious in both bipolar mania and bipolar depression ( 49 ) [3–6 mg in bipolar mania ( 50 ) and 1.5–3 mg in bipolar depression ( 51 )], studies of aripiprazole confirmed efficacy in bipolar mania only ( 52 ). Brexpiprazole studies in bipolar mania were unsuccessful ( 53 ), and, following a positive pilot trial ( 54 ), a RCT in bipolar depression is ongoing ( 55 ). Human PET studies with cariprazine ( 56 , 57 ), aripiprazole ( 58 ), and brexpiprazole ( 58 ) have pointed to the difference potentially explaining these findings: while all three compounds were able to occupy the D 2 receptors in the brain, only cariprazine was able to sufficiently occupy the D 3 receptors as well [( 59 ); Figure 1 ].…”
Section: Dopamine D 2 /D 3 Partial Agonists In the Treatment Of Bd And Sudmentioning
confidence: 99%
“…The primary analyses did not show a statistically significant difference between brexpiprazole and placebo. Brexpiprazole was more efficacious in patients with impaired or no insight (predominantly EU patients) than patients with excellent insight (predominantly US patients) (Vieta et al, 2021). Further studies are necessary to address the potential efficacy of brexpiprazole in acute mania, which should ensure that the study sample is severely ill enough (especially regarding insight), and that the dose/titration schedule is optimal.…”
mentioning
confidence: 99%